2008
DOI: 10.2460/javma.233.4.580
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of auditory and neurologic effects associated with ventral bulla osteotomy for removal of inflammatory polyps or nasopharyngeal masses in cats

Abstract: Results suggested that in cats, VBO for removal of inflammatory polyps or masses is unlikely to affect hearing as measured via air-conducted BAER. Most cats developed short-term Horner syndrome. Cats with deafness prior to surgery did not regain auditory function. Ventral bulla osteotomy to remove nasopharyngeal polyps or masses provided no functional advantage with regard to restoration of hearing, compared with other surgical techniques. Polyp recurrence and long-term adverse effects were uncommon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
2
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 29 publications
1
14
2
2
Order By: Relevance
“…More cats had recurrence of aural IP with simple traction (traction performed without curettage of the tympanic cavity) removal versus surgical intervention, a finding consistent with comparisons from previous reports. [19][20][21][22][23] For those cats where recurrence was documented, use of topical and/or systemic glucocorticoids did not seem to have an impact on time to recurrence. A larger sample size may have yielded different results, as several authors 23 have suggested a relationship between glucocorticoid therapy and lack of recurrence of polyps.…”
Section: Discussionmentioning
confidence: 99%
“…More cats had recurrence of aural IP with simple traction (traction performed without curettage of the tympanic cavity) removal versus surgical intervention, a finding consistent with comparisons from previous reports. [19][20][21][22][23] For those cats where recurrence was documented, use of topical and/or systemic glucocorticoids did not seem to have an impact on time to recurrence. A larger sample size may have yielded different results, as several authors 23 have suggested a relationship between glucocorticoid therapy and lack of recurrence of polyps.…”
Section: Discussionmentioning
confidence: 99%
“…7 Hearing deficits have also been reported in cats, owing to fluid in the TB or damage to the ossicles of the middle ear. 5,11…”
Section: Introductionmentioning
confidence: 99%
“…A default setting with auditory clicks (click duration of 0.1 millisecond) was used. Each recorded BAER was a mean of neural activity after 300 stimuli at 90 dB, normal hearing level 37 . For each test on each dog, a graphic representation of positive and negative peaks denoting the mean neuronal activity resulting from external acoustic stimuli was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Each recorded BAER was a mean of neural activity after 300 stimuli at 90 dB, normal hearing level. 37 For each test on each dog, a graphic representation of positive and negative peaks denoting the mean neuronal activity resulting from external acoustic stimuli was obtained. Each wave represents overall neuronal activity in one or more cortical and subcortical brain structures.…”
Section: Brainstem Auditory Evoked Response Testingmentioning
confidence: 99%